A Study on the Level of Employee Job Satisfaction at TV Sundaram Iyengar and Sons - Palaniswamy, R.; Sripriya, Thiriveni (Gyan Management Journal, 2014)
Any job requires good interpersonal relationship among workers, co-workers and different level managers, following the organizational policies and rules, meeting the organizational goals. Job satisfaction of employees is a vital factor that leads to job performance; and retention of skilled workers. In this article also the authors found that employees in TUSI & SONS Ltd have on an average same level of job satisfaction. The noteworthy fact is that employers'job satisfaction is more influenced by their relationship with superiors then pay and promotion, working conditions and relationship with co-workers.
Keywords: Job Satisfaction; Organizational Commitments; elationship with supervisors